CZARNY CZŁOWIEK SERGIUSZA JESIENINA JAKO TEKST O POJEDYNKU DOBRA ZE ZŁEM. GENEZA. LOSY. INTERPRETACJA - Ojcewicz, Grzegorz (Acta Neophilologica, 2010)
The article presents a new commentary to one of the most popular poems which still evokes most controversy among interpreters – Black Man. To the author the poem is a work of the universal matter embodying the eternal battle of the good and the evil in the Bolshevik’s Russia where everyone kept vigilant watch on everyone. Proving this thesis not only does he develop a detailed analysis but he also exposes sources of the text as well as its complex editing paths that show the developing of Black Man up to the last version. The accomplished statistic analysis of the poem the key words of which are “person” and “black” demonstrates its universality and introduces Yesenin’s work into intercultural dialogue of national literatures on permanent basis.